Lesion Development, Biochemical Changes And Genetic Relationships Associated With Resistance To Colletotrichum Spp. On Chilli Pepper (Capsicum Spp.). - Hidayat, Iteu Margaret (2002)
Chilli pepper (Capsicum spp.) is one of the important vegetable crops, with have attractive features in the fruits: aesthetic quality of aroma, taste, color, texture, and also nutrients, minerals, vitamins and antioxidant properties. Resistance to Colletotrichum spp., causal agent of pre- and post harvest fruit rot diseases on commercial chilli pepper cultivars has not been reported, and screening for resistance could have been a difficult task. Based on lesion development (width, length, percentage of lesion, percentage of sporulation, and rate of lesion development), responses of detached green and red fruits of four lines of chilli pepper (P3, PS, 327 and 146) to spot and wound inoculation with C. capsici and C. gloeosporioides were evaluated in factorial experiments with complete randomized design.